Forest Monitoring Using Remote Sensing Data & ILWIS GIS - Polina Lemenkova (V. M. Bugakov, 2015)
Работа оценивает изменения в типах растительного покрова российского Севера в течение последних двух десятилетий. Результаты прове- денной классификации спутниковых снимкой показывают экологические ас- пекты изменения лесотундровых экосистем. Технически, обработка данных была выполнена в ПО ГИС ILWIS, с использованием методов дешифрирования и контролируемой классификации. Результаты позволяют выявить изменения в типах и распределении растительного покрова. This paper focuses on the assessment of the changes in land cover types in Yamal peninsula over the past two decades, which shows local environmental aspects of the climate change in North. Technically, the data processing was per- formed in ILWIS GIS, using semi-automated methods of image interpretation and supervised classification. The results of the classification analysis enable to identify changes in land cover types and their distribution in Yamal.